Autothermal hydrogen release from liquid organic hydrogen carrier systems - Siegert, Fabian; Gundermann, Michael; Maurer, Lukas; Hahn, Simon; Hofmann, Jonas; Distel, Max; Schühle, Johannes; Müller, Karsten; Wolf, Moritz; Preuster, Patrick; Auer, Franziska; Geißelbrecht, Michael; et al. (International Journal of Hydrogen Energy, 2024)
A typical feature that the LOHC technology shares with other types of chemical hydrogen storage is that the release of hydrogen from the carrier requires an input of heat. In many use cases where waste heat from external sources is not available (e.g. in heavy-duty mobility), this is seen as a major drawback. In this paper, we show that autothermal LOHC dehydrogenation offers a very attractive way to overcome this drawback. In detail, we demonstrate autothermal hydrogen release from dicyclohexylmethane using diphenylmethane oxidation to benzophenone as source of heat. The full storage cycle involves benzophenone hydrodeoxygenation to dicyclohexylmethane, dicyclohexylmethane dehydrogenation to diphenylmethane, and diphenylmethane oxidation to benzophenone. We studied both the individual reaction steps using pure feedstocks and the integral cycle in which the intermediates and by-products of each reaction remain in the system for the subsequent reaction step. Although no efforts have yet been made to develop special catalyst materials for this purpose, the results with the applied commercial hydrodeoxygenation (Pd/C), dehydrogenation (Pt on alumina) and partial oxidation (VOx/TiO2) catalysts are already very promising. The storage cycle can be closed with high selectivity and with only minor total oxidation losses. The proposed concept of autothermal LOHC dehydrogenation offers the potential to increase the amount of useable hydrogen from a given amount of charged hydrogen carrier by up to 30%.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Autothermal hydrogen release; Benzophenone; Benzyltoluene; LOHC; Partial oxidation